2019
DOI: 10.1145/3342286
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Characteristics of Internet Paths

Abstract: Interactive and multimedia applications depend on the stability of end-to-end paths for predictable performance and good quality of service. On the other hand, network providers depend on multiple paths to ensure fault tolerance and use load balancing between these paths to enhance the overall network throughput. In this study, we analyze path dynamics for both end-to-end paths and path segments within service providers’ networks using 2 months of measurement data from the RIPE Atlas platform, which collects p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…While there could be multiple interfaces of a device connected to the same subnetwork to increase its throughput, this is an extremely rare practice. Note that in a recent study [49], we observed that 4.4% of path traces have a routing loop within an autonomous system, but we assume path traces to be loop-free when IP aliases are introduced.…”
Section: Ip Alias Identificationmentioning
confidence: 99%
“…While there could be multiple interfaces of a device connected to the same subnetwork to increase its throughput, this is an extremely rare practice. Note that in a recent study [49], we observed that 4.4% of path traces have a routing loop within an autonomous system, but we assume path traces to be loop-free when IP aliases are introduced.…”
Section: Ip Alias Identificationmentioning
confidence: 99%
“…Several research works have examined the internet characteristics of internet AS and identified threat types on internet AS 11 – 15 . Bakhaliev et al 16 investigated path dynamics for end-to-end paths and path segments using two months of measurement data from the RIPE Atlas platform. They observed that 78% of the end-to-end routes have at least two alternative AS paths starting from 3380 ASs.…”
Section: Related Workmentioning
confidence: 99%
“…To provide some context, in a fat-tree data center network [216], a path between servers within the same pod and di erent pods is 2 and 4 hops, respectively. For wide area networks such as the autonomous system level graph, the median path length lies between 5 and 6 [217]. Note that for the FB-WS trace, we leveraged the meta-data describing a packet's source and destination pod and rack, and correlated that with Facebook's data center network architecture [218] to identify the number of hops.…”
Section: Motivationmentioning
confidence: 99%